WHICH CLINICAL MEASURES ARE MOST APPROPRIATE FOR MEASURING DISEASE PROGRESSION IN PARKINSON'S DISEASE?. Issue 11 (9th October 2013) - McGhee, David; Parker, Alexander; Fielding, Shona; Counsell, Carl
Abstract : Objectives: To determine which clinical measures of disease progression in Parkinson's disease (PD) can feasibly be measured across the disease spectrum and which are most sensitive to change. Background: Understanding the feasibility of measuring clinical outcomes and their sensitivity to change is crucial when choosing outcome measures for trials of putative neuroprotective drugs in PD. Methods: People with clinically deﬁned PD were identiﬁed from an on–going long–term follow–up study of incident parkinsonian patients. Annual follow–up included a motor UPDRS, MMSE, Schwab and England, and a timed–walk. In cases of advanced consent a full UPDRS, timed hand–taps, MMP, PDQ–39, EuroQol–5Dindex, EQ–VAS and the Barthel index were also completed. Using data from consenting patients who completed each annual follow–up, percentage completion of collection for each measure over ﬁve years was examined. In a subset that completed three years of follow–up, linear mixed modelling was used to determine if clinical measures changed signiﬁcantly over time. Sensitivity to change was assessed by grouping the measures (motor impairment, disability, quality of life, and cognition) and comparing the percentage change in each from baseline. Results: Annual percentage completion of all measures (n=203 at baseline) was high (>80%) over ﬁve years. Change over time was examined in 176 patients who had completed three–years of follow–up. All measures, except the stigma (P=0.102) and social (P=0.177) subsections of the PDQ–39, demonstrated signiﬁcant progression over three–years. The PDQ–39 summary index and its subsections were most sensitive to change (motor impairment, PDQ–39 mobility; disability, PDQ–39 ADL; quality of life, PDQ–39 summary index; cognition, PDQ–39 cognition). Conclusions: Collection of all examined clinical measures was feasible. The PDQ–39 summary index and subsections were most sensitive to change.